2011
DOI: 10.1590/s1807-59322011000800019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes on myocardial capillary density and serum angiogenesis biomarkers in male rats

Abstract: INTRODUCTION:Cardiovascular disease is one of the main causes of mortality and morbidity in diabetic patients. This study evaluated the effects of diabetes on myocardial capillary density and several serum angiogenic factors including nitric oxide, vascular endothelial growth factor, and soluble vascular endothelial growth factor receptors.METHODS:Twelve male rats were divided into two groups: control and diabetic (n = 6 each). Diabetes was induced with a single dose of streptozotocin (50 mg/kg). After 21 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…[4344] High levels of VEGF-A also lead to vascular permeability in the glomeruli,[45] Physiological levels of NO (nitric oxide) creates low vascular permeability but NO levels too high or too low can lead to hyper-permeability that in turn lead to glomerular injury and diabetic nephropathy. [39]…”
Section: Introductionmentioning
confidence: 99%
“…[4344] High levels of VEGF-A also lead to vascular permeability in the glomeruli,[45] Physiological levels of NO (nitric oxide) creates low vascular permeability but NO levels too high or too low can lead to hyper-permeability that in turn lead to glomerular injury and diabetic nephropathy. [39]…”
Section: Introductionmentioning
confidence: 99%
“…[9] Furthermore, it is suggested that VEGF to sVEGFR-1 ratio is a better marker for evaluation of angiogenesis status. [2122] Thus, in the present study, we measured VEGF: sVEGFR1 ratio and we found that this ratio was decreased after BIIE0742 treatment in normal and obese animals. On the other hand, serum NO concentration was also decreased in treatment groups.…”
Section: Discussionmentioning
confidence: 51%
“…As, angiogenesis and capillary density decreases in heart of diabetic rats. 18 Similarly, clinical studies have shown an abnormality in endothelium dependent vasodilation in patients with diabetes. 19 Diabetes has been shown to cause structural and functional disturbances in the myocardium through myocardial fibrosis, collagen formation, myocyte hypertrophy, mitochondrial dysfunction, and ROS accumulation.…”
Section: Discussionmentioning
confidence: 98%